Slavery on trial: race, class and criminal justice in Antebellum Richmond, Virginia - Campbell, James M. (New perspectives on the history of the South, 2007)
Abandoned to causes of corruption : slave life and policing in the city -- "An evil which demands a speedy remedy" : white criminality in an urban slave society -- "The victim of prejudice and hasty consideration" : slave trials, clemency, and punishment -- "With these poor rogues their judge had never dined" : honor, law, and the trial and punishment of white criminals -- The "stigma, of the deepest degradation, was fixed upon the whole race" : free African Americans and the criminal justice system